A metamorfose da sereia: um caminho para a narrativa estendida do audiovisual publicitário - MACHADO, Guilherme Leite (2017)
A new communication tool has emerged over the past two decades, transforming the advertising landscape and captivating a part of the viewer / consumer audience. Such a model differentiates itself by using serial narrative complexity with veiled commercial objectives (sometimes not so much). The objective of this study is to map the characteristics of this model that mixes advertising and entertainment - advertainment - used by companies since the beginning of the 21st century. To understand this phenomenon, there are three series that have come to take advantage of this new model as a way to enchant their audience with more emotional appeal: the precursor series The Hire, produced by the German automaker BMW; the web series What Lives Inside, a partnership between the Intel and Dell technology products industries; and the #No Gogó national production commissioned by AmBev, the world leader in beverages, for its Antarctica brand.